Systematic Review: Faktor-Faktor Yang Memengaruhi Pelayanan Keperawatan di Penyedia Pelayanan Primer - Deby Zulkarnain Rahadian Syah; Rr. Tutik Sri Hariyati; Hanny Handiyani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: Primary level health facilities such as Puskesmas, doctor's practices, and primary clinics function as gatekeepers, namely controlling the use and referral of participants. Primary service providers are comprehensive, namely promotive, preventive, curative, and rehabilitative.Objective: Identifying research results to find out what factors can increase patient satisfaction with nursing services at primary health care providers.Methods: This research method uses a Systematic Literature Review with the limitation of articles published in the last two years from 2020-2021. Keywords in the search for nursing service, patient satisfaction, and primary care were analyzed using the PRISMA approach. Article search database using PubMed, ProQuest, and ScienceDirect.Results: The results obtained were 280 articles, 13 articles double found, the suitability for the title was 54 articles, the inclusion criteria screening and completeness of the abstracts found to be nine articles. Analysis of nine articles on factors that influence primary nursing services internally, namely the level of education, courtesy and respect, maintaining privacy, care and counseling, quality of care, management and leadership of the head nurse, and discipline of nursing staff. Health care facilities, health insurance, lack of equipment or infrastructure, long waiting times, lack of health workers, limited operating hours of health care, hygiene, decline in primary care providers, increasing aging population with limited health insurance, decreased access to health care, careers individuals who quit, the practice environment, e-Health counseling technology, the relationship between nurses and doctors, and comfortable facilities are external factors.Conclussion: It was found that the factors that influence primary nursing services are divided into two aspects, namely internal and external.